Prostate stem cell antigen gene TT genotype and development of intestinal metaplasia in Helicobacter pylori infection. Issue 1 (January 2016) - Uotani, Takahiro; Sugimoto, Mitsushige; Ichikawa, Hitomi; Tanaka, Shingo; Nagashima, Hiroyuki; Uchida, Tomohisa; Graham, David Y.; Yamaoka, Yoshio
Abstract : Objectives: Gastric cancer is etiologically related to interactions between Helicobacter pylori (H. pylori) infection, environmental and host factors. Gastric carcinoma is associated with a cascade of increasing atrophic gastric mucosal damage. Prostate stem cell antigen ( PSCA ) polymorphisms have been associated with an increased risk of gastric cancer. We aimed to examine the interaction between PSCA polymorphisms and H . pylori in the progression of H. pylori ‐related gastritis. Methods: The genotypes (TT, TC and CC) of PSCA single nucleotide polymorphism rs2294008 among H . pylori infected and uninfected Bhutanese were compared with the severity of H. pylori ‐related gastritis [neutrophils, monocytes, atrophy scores, H . pylori density, and the presence and extent of intestinal metaplasia (IM)] using the updated Sydney system. Results: Biopsies from 339 participants were included. The proportion of biopsies with IM was significantly ( P < 0.05) greater in those with the TT genotype than in either those with the CT or CC genotype. Although no significant differences were found in inflammation or H . pylori density scores, the scores for IM at both gastric corpus and antrum among participants infected by H . pylori with the TT genotype was significantly ( P < 0.05) greater than in the C allele carriers. Conclusion: PSCA TT genotype is associated with a more than a threefold increase in the prevalence and the extent of gastric mucosal IM compared to C allele carriers among H . pylori ‐infected Bhutanese.